Upaya Menumbuhkan Minat Wirausaha Kaum Muda Melalui Pelatihan Peningkatan Nilai Tambah Produk Olahan Ubi Kayu di OMK (Orang Muda Katolik) - Agustian, Efandri; Kurniawati, Merlyn; Nurfadhilah, Lia; Marisi, Marisi; Immanuel Sihombing, Midian (Abdimas Mandalika, 2025)
Abstract:  This community service activity focuses on fostering youth entrepreneurship interest through training in increasing the added value of processed cassava products. Where cassava is a local resource in Umakatahan Village, Malaka Regency. The activity was attended by 3 lecturers, 2 speakers supported by 2 students. The training participants were 35 people, consisting of the Management and members of OMK (Orang Muda Katolik) of Umakatahan Village, Malaka Regency. Two speakers in this activity are experts in the field of Entrepreneurship and marketing, especially Digital Marketing. This community service activity has been able to increase the interest and knowledge of the young generation of Umakatahan Village. This program has succeeded in motivating young people to be more professional in managing agricultural products and adapting to market needs.Abstrak: Tujuan Kegiatan pengabdian kepada masyarakat ini menitikberatkan pada pembinaan minat berwirausaha pemuda melalui pelatihan peningkatan nilai tambah produk olahan singkong. Dimana singkong merupakan sumber daya lokal di Desa Umakatahan Kabupaten Malaka. Kegiatan ini diikuti oleh 3 orang dosen, 2 orang pemateri dengan dukungan 2 orang mahasiswa. Peserta pelatihan berjumlah 35 orang yang terdiri dari Pengurus dan anggota OMK (Orang Muda Katolik) Desa Umakatahan Kabupaten Malaka. Dua orang pemateri dalam kegiatan ini merupakan pakar dalam bidang Kewirausahaan dan pemasaran khususnya Digital Marketing. Kegiatan pengabdian kepada masyarakat ini telah mampu meningkatkan minat dan pengetahuan generasi muda Desa Umakatahan. Program ini berhasil memotivasi generasi muda untuk lebih profesional dalam mengelola hasil pertanian dan beradaptasi dengan kebutuhan pasar.